Pengembangan Sistem Informasi Toko Bangunan (Studi Kasus: UD Darmo Jaya) - Satriyo Putra Sarjono; Satrio Agung Wicaksono; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
UD Darmo Jaya is currently a company engaged in the sale of building materials such as wood, iron, galvalum, nails, and others that can sell up to large scale to almost all of Indonesia. Based on the result of the interview, UD Darmo Jaya has some problems on sales transaction and warehousing activities. The problems that UD Darmo Jaya possesses include the stacking of nota and surat jalan, customers who forget to settle their debts, calculate the remaining stock of goods take a lot of time, recording transactions done after hours of work, and branch heads who do not record the goods. The method used in system development is Throw-away Prototyping where the method is chosen because it can help the stakeholders to get a desired system to be able to solve the problem. In this research we got 81 functional requirement and 1 non functional requirement obtained from 1 time iteration. From the results of black-box testing, obtained a result of 100% valid of 81 test cases tested. Based on compatibility testing, the tested system is capable of running on many different browsers, especially in the microsoft edge and android browsers. Based on testing of user acceptance testing of 3 types of testers (owner, cashier, and branch head) produces an average percentage of 80% stating that the system meets the functional requirements, and can assist in running business processes at UD Darmo Jaya mainly on sales and warehousing.